2015
DOI: 10.1007/s10337-015-2849-3
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay-Guided Separation and Identification of a New Anti-Lung Cancer Compound from Cordyceps militaris by Means of Off-Line Two-Dimensional Preparative Chromatography, Real-Time Cell Analysis, and X-ray Single-Crystal Diffraction

Abstract: has much potential for purification of other weakly polar compounds and could enable purification of other traditional Chinese medicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…By combining chromatography with biological activity detection, the active compounds were enriched to obtain high activity pure compounds [ 3 , 4 ]. Bioactive compounds, including antimicrobial coumarins, anti-lung cancer compound, and water-soluble antioxidants, have been successfully isolated by BGS [ 5 , 6 , 7 ]. Counter-current chromatography, as the most vital chromatographic technique in BGS, is often used for the separation of various active compounds from natural plant resources [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…By combining chromatography with biological activity detection, the active compounds were enriched to obtain high activity pure compounds [ 3 , 4 ]. Bioactive compounds, including antimicrobial coumarins, anti-lung cancer compound, and water-soluble antioxidants, have been successfully isolated by BGS [ 5 , 6 , 7 ]. Counter-current chromatography, as the most vital chromatographic technique in BGS, is often used for the separation of various active compounds from natural plant resources [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, bioactivity-guided separation has gradually attracted the attention of researchers and it can be considered to be a process including a series of steps to locate the active compounds before the separation. Successful examples can be seen in the discovery of compounds with κ-opioid receptor agonist activities in Corydalis yanhusuo W. T. Wang [11] and anti-lung cancer compounds from Cordyceps militaris [12]. With the aid of the active screening of the fractions separated by HPLC, some of the components with outstanding activity can be locked, and then be separated again by prep-HPLC to obtain the active compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In the studies about Cordyceps sp., a lot of bioactivities have been reported, such as immunomodulatory activity, antioxidant activity, anti-tumor activity, and cancer cell cytotoxicity. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Cordyceps militaris is a valuable specie of the genus Cordyceps. It parasitizes lepidopteran pupa and forms fruiting bodies.…”
mentioning
confidence: 99%
“…Although several biological and chemical studies about the mycelia and the fruiting bodies have been reported, there are few studies about its host, lepidopteran larvae infested with the fungus. 4,7,8,10,12,13,[15][16][17][18][19][20] In the screening experiments, we found the cytotoxicity of the crude extracts of Bombyx mori inoculated with C. militaris and started this study.…”
mentioning
confidence: 99%
See 1 more Smart Citation